Socio-economic empowerment of the Tengkurak Village society through education assistance and social media-based digital marketing training - Rudhy Ho Purabaya; Kraugusteeliana Kraugusteeliana; Artika Arista (Community Empowerment, 2022)
It is crucial to boost the industry's capabilities and competitiveness in light of the swiftly evolving global market competition. Digital technology is rapidly developing in a variety of fields. Therefore, the service conducts education and training assistance activities for digital-based marketing as a means of concern and implementation of cooperation with partners. The team prepared video tutorials and digital marketing modules with Facebook. After participating in the program, the Tengkurak Village community gained new knowledge and understanding regarding Digital Marketing with Facebook and its use. This is based on the evaluation's finding which revealed thatthere was an increase in understanding of Facebook-based digital marketing by 40%.